Handover queuing strategies with dynamic and fixed channel allocation techniques in low Earth orbit mobile satellite systems - Del Re, E.; Fantacci, R.; Giambene, G. (IEEE transactions on communications, 1999)
This paper deals with the performance evaluation of various resource management strategies that are suitable for low Earth orbit mobile satellite systems (LEO-MSSs). A user mobility model has been proposed and its statistical parameters have been derived. Both fixed channel allocation (FCA) and dynamic channel allocation (DCA) techniques have been considered. Moreover, in order to reduce the handover failure probability, we have assumed that interbeam handover requests which do not immediately obtain service can be queued. In particular, two different queuing disciplines have been compared: (a) the first input first output (FIFO) scheme and (b) a new technique called last useful instant (LUI) which is based on the knowledge of the maximum time within which the handover procedure must be accomplished. Implementation aspects for the LUI technique in a LEO-MSS have been discussed also in comparison with the measurement-based priority scheme (MBPS), previously proposed in the literature on this subject. The efficiency of the LUI queuing scheme as regards the FIFO technique has been investigated by simulations for both DCA and FCA techniques. An analytical approach has been also presented in order to allow the performance evaluation of the FCA scheme with different handover queuing disciplines.